Clinical and Radiological Evaluations of COVID‐19 Patients With Anosmia: Preliminary Report. (11th August 2020) - Lechien, Jerome R.; Michel, Justin; Radulesco, Thomas; Chiesa‐Estomba, Carlos M.; Vaira, Luigi A.; De Riu, Giacomo; Sowerby, Leigh; Hopkins, Claire; Saussez, Sven
Abstract : Objectives/Hypothesis: To investigate clinical and radiological features of olfactory clefts of patients with mild coronavirus disease 2019 (COVID‐19). Study Design: Prospective non controlled study. Methods: Sixteen COVID‐19 patients were recruited. The epidemiological and clinical data were extracted. Nasal complaints were assessed through the 22‐item Sino‐Nasal Outcome Test. Patients underwent psychophysical olfactory testing, olfactory cleft examination, and computed tomography (CT) scans. Results: Sixteen anosmic patients were included. The mean Sniffin' Sticks score was 4.6 ± 1.7. The majority of patients had no endoscopical abnormality, with a mean olfactory cleft endoscopy score of 0.6 ± 0.9. The olfactory clefts were opacified in three patients on the CT scan. The mean radiological olfactory cleft score was 0.7 ± 0.8. There were no significant correlations between clinical, radiological, and psychophysical olfactory testing. Conclusions: The olfactory cleft of anosmic COVID‐19 patients is free regarding endoscopic examination and imaging. The anosmia etiology is not related to edema of the olfactory cleft. Level of Evidence: 4 Laryngoscope, 130:2526–2531, 2020